Evaluasi Program Edukasi dengan Video dan Poster Terhadap Perilaku Masyarakat dalam Menghadapi COVID-19 (Preliminary Study) - Layalia Azka Rahmatina; Meira Erawati (Master of Nursing, Faculty of Medicine, Universitas Diponegoro, Indonesia, 2020)
Introduction: The Indonesian government has issued public health protocols to deal with the corona virus disease 19 (COVID-19). In fact, this rule has been violated by many people. Health education through BARONA program may increase public understanding of disease so that their behavior will change. The purpose of this study was to evaluate the effect of providing education with videos and posters on people's behavior in dealing with COVID-19. Methods: This study was a preliminary study involving twenty adults selected using a purposive sampling in a residential area. Respondents were given health education using posters and videos, then counted the number of respondents who showed health behavior before and after education. The data are then displayed in the frequency distribution table. Results: The results of this study illustrate that there is an increase in the number of respondents who show the behavior of washing hands and wearing masks while traveling. Whereas in the behavior of traveling and keeping a distance from other people, there was no change. Conclusion: Health education using posters and videos can change people's behavior in dealing with COVID-19.